DETERMINATION OF THE AMOUNT OF RESIDUAL PESTICIDES IN THE LIVER TISSUE OF RATS POISONING WITH HALOXYPHOP-R-METHYL AND INDOSACARB PESTICIDES (Journal of Pharmaceutical Negative Results, 2022)
An aqueous solution of the pesticides Galoxyfop-R-methyl and indoxacarb was administered to laboratory white rats by gavage per os at a dose of the LD50 1/10, and the residue in the liver of rats on the 5th, 10th, 20th, 30th, and 40th days after poisoning. the amount of pesticides was determined using APCI (Atmospheric pressure chemical ionization) method. According to the obtained results, the highest concentration of residual pesticides was determined on the 5th day after rats were poisoned. A HPLC MS (6420) Triple Quad LC/MS (Agilent Technologies, USA) was used for analysis.